Portfolio Selection with Heavy Tails - Namwon Hyung; Casper G. de Vries (Tinbergen Institute, 2005)
Consider the portfolio problem of choosing the mix between stocks and bonds under a downside risk constraint. Typically stock returns exhibit fatter tails than bonds corresponding to their greater downside risk. Downside risk criteria like the safety first criterion therefore often select corner solutions in the sense of a bonds only portfolio. This is due to a focus on the asymptotically dominating first order Pareto term of the portfolio return distribution. We show that if second order terms are taken into account, a balanced solution emerges. The theory is applied to empirical examples from the literature.
Keywords: G11; 330; safety first; heavy tails; portfolio diversification; Portfolio-Management; Entscheidung bei Risiko